Strategi Diskursif dalam Reportase Gaya Kampanye Capres Indonesia No. 2 oleh Tirto.Id - Andriani, Cindy (Research Community for Critical Society and Environment, 2024)
Election moments always present a war of discourse as a weapon in political contestation to shape opinions. The narrative contained in a discourse is constructed by discursive strategies that can influence public perception of the election. Therefore, this study aims to (1) explain the discursive strategies used by tirto.id in conveying the campaign style reportage of Presidential Candidate Number 2 and (2) explain the historical context behind the discursive strategies used by tirto.id. This study is a qualitative descriptive study with a historical discourse analysis approach. Data collection was carried out using the listening and recording method. The data source is Instagram tirto.id about the campaign style reportage of Presidential Candidate Number 2 with the title